The Restraint Mechanism of High-Strength Rectangular Spiral Stirrup Confined Fiber Reinforced Concrete - Pengyu Fan; Huajing Zhao; Weitong Liu (Buildings)
To reveal the confinement mechanism of high-strength rectangular spiral stirrups (HRSSs) on fiber-reinforced concrete, this study designed and conducted axial compression tests on 20 HRSS-confined fiber-reinforced concrete columns. The effects of stirrup spacing, stirrup strength, and concrete strength on the strength and ductility of the columns were analyzed. The experimental results demonstrate that HRSS can significantly improve the performance of fiber-reinforced concrete. The peak strength of concrete exhibited a maximum increase of 2.033 times, and the ductility ratio achieved a maximum increase of 2.588 times. Furthermore, the application of densely spaced high-strength spiral hoops to confine the core concrete not only effectively enhances its compressive strength but also markedly improves its deformability. Based on the stress distribution across the cross-section of HRSS-confined fiber-reinforced concrete columns, this paper proposes a method for delineating the effective confinement area, establishes calculation models for effective lateral confinement stress, effective confinement coefficient, peak stress, and peak strain, and develops a stress-strain constitutive relationship suitable for HRSS-confined fiber-reinforced concrete columns.